The concept of "exigüidad" of the crime: dogmatic and criminal politics perspectives (2011)
Through the analysis of criminal reflection of the main enlightened philosophers, the author wants to show different arguments that from those positions can be given to the use of the penalty as a State’s mechanism, pointing out how dissimilar starting po